Assessment and communication excellence for safe patient outcomes (ACCELERATE): A stepped-wedge cluster randomised trial protocol. Issue 5 (October 2022) - Rihari-Thomas, John; Whittam, Susan; Goncharov, Liza; Slade, Diana; McElduff, Benjamin; Pritchard, Tanya; McMahon, Jake; Coventry, Alysia; Coughlan, Kelly; Steadward, Yvonne; Taylor, Joanne; Thornton, Anna; et al.
Abstract: Background: Nurses play a major role in patient safety. Poor nursing assessment and communication practices are associated with higher incidence of the adverse events of undetected deterioration, falls, and pressure injuries. Despite widespread adoption of patient safety systems, occurrence of these events continues. Aim: To implement and evaluate the feasibility and effectiveness of an organisational ward-level intervention to facilitate comprehensive systematic assessment and improved communication in clinical handover to reduce medical emergency team calls; unplanned Intensive Care Unit admissions; falls; and pressure injuries. Design: A stepped-wedge cluster randomised trial sequentially implemented over 12 months. Methods: Evidence-based implementation strategies will be employed to support implementation of an intervention focusing on comprehensive systematic patient assessment and improved nurse bedside clinical handover and multidisciplinary communication involving the patient. These are – intervention tailoring to individual wards through barrier and enabler identification; action plans; education; clinical champions; outreach visits; facilitation; clinician engagement; and reminders. Primary outcome measures will be a composite of Medical Emergency Team calls and unplanned intensive care unit admissions for deterioration. Secondary outcomes will be all categories of inpatient falls; stage 2–4 pressure injuries; nurse-reported perceptions of: teamwork; safety culture, and engagement; and patient-reported experience measures of receiving safe and patient-centred care. An a priori process evaluation will determine factors influencing intervention uptake and inform strategies for future upscale and spread. Discussion: This feasibility trial will provide evidence regarding the use of systematic comprehensive patient assessment, combined with clinical handover re-design involving patients, to reduce clinical deterioration, falls and pressure injuries.